Towards a Resilient Generation: Integrating Digital Music Education with Disaster Mitigation in Bukittinggi Schools - Handayani, Lucy; Wadiyo, Wadiyo; Suharto, Suharto (Universitas Negeri Semarang, 2025)
This study explores the integration of digital music education with disaster mitigation efforts in senior high schools in Bukittinggi, Indonesia, as a strategy to foster disaster awareness and preparedness among students. Amid the increasing frequency of natural disasters in the region, there is a growing need for educational innovations that connect creative expression with practical life skills. The research aims to investigate how music-based learning—enhanced by digital technology—can be utilized as a medium for disaster education. Using a qualitative approach supported by surveys, interviews, classroom observations, and analysis of student projects, this study reveals that students show a strong interest in incorporating disaster themes into their digital music compositions. The use of Digital Audio Workstations (DAWs) not only enhances student creativity but also allows them to express their understanding of disaster preparedness through culturally relevant music. Collaboration with local artists and disaster management institutions has further strengthened the contextual relevance of the learning process. However, limitations such as inadequate infrastructure, limited access to technology, and a lack of technical training remain significant challenges. The findings suggest that a curriculum integrating digital music education with disaster mitigation content has great potential to contribute to the formation of a resilient generation. To maximize its impact, the study recommends government support in improving digital infrastructure and teacher training programs.